(untitled) - Gee, Sherman (New York, 1981)
This book gives readers insight into impact of technology on America's economic and security interests, and it underscores the importance of developing a balanced two-way flow of technology across our borders.
Keywords: Chuyển đổi công nghệ,Technology transfer